Penataan Koridor Jl. H. Juanda Marga Mulya, Kec. Bekasi Utara, Kota Bekasi, Jawa Barat - Retno Fitri Astuti; Putri, Isria Miharti Maherni; miarsono, Harry; Anggodo, Jamas Siaga; Muhlis, Muh. (DPPM Universitas Pelita Bangsa, 2023)
Jln. H.juanda is a transit point for users of rail transportation services at Bekasi station with high mobility. Activities on Jalan H. Juanda are dominated by motorbikes, shop houses, and street vendors. The actors involved in this area are users of rail transportation services, entrepreneurs around the station environment, street vendors (street vendors), drivers (motor cars, public transport), pedestrians. In this area there is a meeting between pedestrians and motorized vehicles. This area is a traffic jam point in Bekasi because there is a rail gate that is close to the sharp bamboo monument roundabout. Under these conditions, it is necessary to organize along the H. Juanda road corridor to overcome the congestion that occurs and to design a road corridor that accommodates all existing activities and actors. The arrangement begins with a field survey to identify problems, collect data and measure existing in the field. These data are then analyzed using Hamid Sirvani's Urban Design theory, taking into account the applicable regulations and standards. The output of this arrangement is the corridor design for Jln. H. Juanda includes the design of pedestrian circulation paths, public and private vehicle drivers, paths and street vendor zones. Design output includes two-dimensional (2D) and three-dimensional (3D) layout drawings.